2019
DOI: 10.1002/slct.201902344
|View full text |Cite
|
Sign up to set email alerts
|

Solvents Effect on the Morphology and Stability of Cu/CuO Nanoparticles Synthesized at High Fluence Laser Ablation

Abstract: Cu/CuO NPs were synthesized by ablating Cu target using nanosecond Nd:YAG pulsed laser operating at 1064 nm with 8 ns pulse duration in three different solvents viz: ethylene glycol (EG), deionized water (DI) and ethanol (Eth). The effects of these three solvents at high laser fluence of 40 J/cm 2 was investigated to study the stability and morphology of nanoparticles using microscopic and spectroscopic techniques. The morphology of these nanoparticles are dependent on the physical properties of solvents (like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Previous works have reported that laser ablation of a copper target in DDW and ethanol leads to the formation of CuO NPs. [53][54][55] However, in this theoretical investigation, the nucleation of CuO in DDW could not be examined due to constraints related to the dielectric constant k l . 56 The pulsed laser ablation of copper in acetone results in the NPs getting surrounded by a carbon matrix which prevents NP oxidation.…”
Section: Implication Of Application Of An External Electric Field On ...mentioning
confidence: 99%
“…Previous works have reported that laser ablation of a copper target in DDW and ethanol leads to the formation of CuO NPs. [53][54][55] However, in this theoretical investigation, the nucleation of CuO in DDW could not be examined due to constraints related to the dielectric constant k l . 56 The pulsed laser ablation of copper in acetone results in the NPs getting surrounded by a carbon matrix which prevents NP oxidation.…”
Section: Implication Of Application Of An External Electric Field On ...mentioning
confidence: 99%
“…is red shift can be attributed to the variation of crystallinity of the doped polymer [32]. Also, a shoulder-like band is observed at 270 nm which has been attributed to the characteristic peak of CuONPs [36]. 1) was used to calculate the absorption coe cient, α(]), as well as each curve near the edges [37]:…”
Section: Optical Propertiesmentioning
confidence: 99%
“…In addition, amendments in the design of hybrid SERS substrate by integrating plasmonic NSs for the fabrication of nanophotonic devices have also been illustrated. In addition, a review by Schlucker and Fan explored the concepts and magnitudes of different assemblies of plasmonics in chemical applications. , According to the advancements of plasmonics, SERS has triggered intense attention because of its investigations and applications in different fields such as biology, chemistry, medicine, and environmental protection owing to its intrinsic features like high sensitivity and single molecular sensing capability. The schematic representation of the Raman scattering phenomena on a metal decorated Si-based surface is shown in Figure . The Si-based surfaces (i.e., Si and its NSs) are very commonly used as a base/template for the fabrication of operative SERS-active substrates, which is due to its extensive connection and relevance in the electronics and optoelectronics industry.…”
Section: Introductionmentioning
confidence: 99%